Integrating Climate Change Issues into Biology Instruction to Enhance Preservice Biology Teachers' Climate Literacy and Systems Thinking - Rikardus Herak; Lukas Seran (PT ARRUS Intelektual Indonesia, 2026)
This study examines the effectiveness of biology instruction integrating climate change issues in enhancing preservice biology teachers' climate literacy and systems thinking. The study employed a quantitative approach using a quasi-experimental pretest-posttest control group design. The sample comprised 60 preservice biology teachers assigned to an experimental class and a control class, with 30 participants in each group. The experimental class received biology instruction integrated with climate change issues, whereas the control class received conventional instruction. Data were collected through a climate literacy test and a systems thinking test and analyzed using descriptive statistics, multivariate analysis of covariance (MANCOVA), and follow up univariate analysis of covariance (ANCOVA). The results reveal a significant difference between the two groups in the combined posttest scores of climate literacy and systems thinking after controlling for pretest scores, indicated by Wilks' Lambda = 0.302, F(2, 55) = 63.48 p < 0.001 Follow up analyses showed significant effects on climate literacy, F(1, 57) = 84.3 p < 0.001 , partial ?² = 0.597 and systems thinking, F(1, 57) = 56.23 p < 0.001 partial ?² = 0.497 The findings confirm that integrating climate change issues into biology instruction effectively strengthens preservice biology teachers' climate literacy and systems thinking.